The Relation of Buddhism and Laws in Thai Society From Pre-Ayutthaya Period-A. D. 1932 - Chutikamo, Yodchai (Suan Dusit Graduate School Academic Journal, 2024)
This article aimed to examine the relation between Buddhism and laws in Thai society which was long distance to each other, in Ayutthaya period and before. When the Thai state evolved from traditional state to modern state, the relation between Buddhism and laws came closer. Buddhism text and principle were not used as laws directly. Buddhism doctrine mainly influenced the morality of the ruler. If the ruler had moral in his mind, the society will be justified. Until the period of Thonburi and Early Rattanakosin, that the rulers used the law to control the Buddhist monks in the country because of the many undisciplined behavior monks. By using of laws to the monks, the monk society came to be controlled by the state steadily. When Thailand was transformed to be Absolute Monarchy state, the monks were controlled by not only Buddha’s word in Tripitaka but also the laws of the state. Buddhism was raised to be the national religion, indirectly, by “The Palace Law of Succession, Buddhist Era 2467” that The King of Thailand must serve as The Upholder of Buddhism.